ANALYSIS OF SEVENTH-GRADE JUNIOR HIGH SCHOOL MATHEMATICS TEXTBOOKS ON ALGEBRA USING THE PRAXEOLOGY APPROACH - Panjaitan, M. Azhari; Naufal, Nasrul; Herman, Tatang (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
Algebra material in mathematics learning plays a crucial role as the foundation for abstract thinking among junior high school students. However, obstacles in task design in textbooks often hinder students' understanding of basic algebra concepts. This study aims to analyze the algebra material in Grade VII mathematics textbooks using a praxeological approach. The research method employed is qualitative descriptive, consisting of observation through selection, categorization, coding, and in situ analysis. The analyzed textbook is the Grade VII Mathematics book published by the Ministry of Education and Culture in the 2017 revised edition. It was chosen due to its widespread use in schools across Indonesia. The main findings indicate that among the four task designs analyzed, many present epistemological and didactic obstacles, such as a lack of emphasis on fundamental algebra concepts and the presentation of unsystematic material. As a solution, this research proposes an alternative task design that focuses on contextual illustrations, independent exploration, and visualizations to enhance learning effectiveness. Although empirical validation has not yet been conducted, the findings provide a foundational framework for developing better algebra learning materials in the future. The implications of this research are expected to assist textbook developers and teachers in creating content that more effectively supports student learning.